VALUATION ANALYSIS OF GREEN ENERGY SECTOR ISSUERS USING THE DISCOUNTED CASH FLOW METHOD - Wiji Saputra; Mangasi Sinurat; Willy Cahyadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the intrinsic value of green sector issuers. energy listed on the Indonesia Stock Exchange using the Discounted method Cash Flow (DCF) with Free approach Cash Flow to Firm (FCFF). The study used a descriptive quantitative method with a sample of four companies, namely PT Pertamina Geothermal Energy Tbk (PGEO), PT Barito Renewables Energy Tbk (BREN), PT Arkora Hydro Tbk (ARKO), and PT TBS Energi Utama Tbk (TOBA). The data used were secondary data in the form of annual financial reports for the period 2023–2025, while the assessment was carried out through FCFF calculations, cash flow projections, Weighted Average Cost of Capital (WACC), Terminal Value , and intrinsic value of shares. The results show that PGEO has an intrinsic value of Rp2,274 per share, higher than the market price of Rp1,055, so it is categorized as undervalued . Conversely, BREN and ARKO have intrinsic values of Rp1,134 and Rp1,210 per share, respectively, which are below the market price, so they are categorized as overvalued . Meanwhile, TOBA cannot be adequately valued using the DCF method because it produced a negative FCFF in the last year of observation. This study shows that the DCF method is more effective when applied to companies that have positive and stable FCFF, so it can provide a more representative estimate of intrinsic value as a basis for investment decision making.